Marketing : real people, real choices - Solomon, Michael R.; Marshall, Greg W.; Stuart, Elnora W (Boston Prentice hall, 2012)
For undergraduate Principles of Marketing courses. Marketing: Real People, Real Choices is the only text to introduce marketing from the perspective of real people who make real marketing decisions at leading companies everyday.
Keywords: Marketing